Removing Redundant Refusals: Minimal Complete Test Suites for Failure Trace Semantics - Gazda, Maciej; Hierons, Robert M. (Proceedings of the 36th Annual ACM/IEEE Symposium on Logic in Computer Science, 2021)
We explore the problem of finding a minimal complete test suite for a refusal trace (or failure trace) semantics. Since complete test suites are typically infinite, we consider the setting with a bound ℓ on the length of refusal traces of interest. A test suite T is thus complete if it is failed by all processes that contain a disallowed refusal trace of length at most ℓ.The proposed approach is based on generating a minimal complete set of forbidden refusal traces. Our solution utilises several interesting insights into refusal trace semantics. In particular, we identify a key class of refusals called fundamental refusals which essentially determine the refusal trace semantics, and the associated fundamental equivalence relation. We then propose a small but not necessarily minimal test suite based on our theory, which can be constructed with a simple algorithm. Subsequently, we provide an enumerative method to remove all redundant traces from our complete test suite, which comes in two variants, depending on whether we wish to retain the highly desirable uniform completeness (guarantee of shortest counterexamples).A related problem is the construction of a characteristic formula of a process P, that is, a formula Φ P such that every process which satisfies Φ P refines P. Our test generation algorithm can be used to construct such a formula using a variant of Hennessy-Milner logic with recursion.